YSK2 Type Dehydrin (SbDhn1) from Sorghum bicolor Showed Improved Protection under High Temperature and Osmotic Stress Condition - Halder, Tanmoy; Upadhyaya, Gouranga; Ray, Sudipta (Frontiers in Plant Science, 2017)
YSK2 type dehydrin from Sorghum bicolor (SbDhn1) showed a high level of transcript accumulation when subjected to high temperature and osmotic stress. The high transcript level occurring in such stress situation might lead to a protective effect; though the exact mechanism by which this is achieved remains poorly understood. Nevertheless, our results provide compelling evidence to prove that transgenic tobacco lines overexpressing SbDhn1 gene showed improve stress tolerance as assessed by reduced membrane damage and low MDA content. Furthermore, we demonstrate here SbDhn1 expressing lines were only able to recover after stress treatment. In this study, we have provided direct evidence for the protection rendered by SbDHN1 protein to a temperature-sensitive enzyme under both high temperature and desiccation stress. We extended this analysis to the whole plant proteome where the addition of SbDHN1 protein helped in retaining the solubility of the protein was demonstrated. Interestingly, in vitro experiments carried out with lactate dehydrogenase (LDH), showed aggregate formation upon subjecting it to high temperature. However, in presence of SbDHN1 protein very few aggregates were observed. Aggregation assay showed a high level of aggregates in wild-type or empty vector transformed plants as compared to SbDhn1 transgenic lines. Confocal microscopy images in leaf peel sections of wild-type plants showed high amounts of aggregates as compared with transgenic lines. This study provides evidence for the protection rendered by SbDHN1 protein under high temperature by inhibiting the aggregate formation and provide the rational for the mechanism how these proteins ameliorate the adverse stress conditions.